Establecimientos turísticos inclusivos y Atención al cliente en el cantón Guano, provincia de Chimborazo. - Broncano Broncano, Brayan Alexander (2024)
The main objective of this research was to analyze the relationship between inclusive tourist lodging establishments and customer service in the Guano canton, province of Chimborazo. This study, characterized as a documentary, descriptive research with a quantitative approach, underscores the need for a comprehensive approach to customer service. Two surveys were conducted using a measurement method (Likert scale), with a determined population. The independent variable was represented by 30 employees of the registered lodging establishments in the Guano canton, while the dependent variable, customer service, was assessed through the perspectives of 243 tourists who stayed in the lodging establishments. The study, while not establishing a direct relationship between tourist inclusion and the quality of customer service in Guano Canton, Chimborazo, highlights the multifaceted nature of customer service. It underscores that customer service is influenced by additional factors such as staff training, personalization of services, and the creation of a welcoming environment for all tourists. In other words, accessibility in establishments does not guarantee quality customer service. The research culminates in a proposal called Training Manual: “Accessible and Inclusive Tourism: Opportunities and Challenges for the Ecuadorian Tourism Sector”, which advocates for a comprehensive approach to customer service.